Do rates of unprotected anal intercourse among HIV-positive MSM present a risk for hepatitis C transmission?. Issue 5 (8th June 2011) - Stall, Ron; Wei, Chongyi; Raymond, H Fisher; McFarland, Willi
Abstract : Objectives: To compare the rates of unprotected anal intercourse (UAI) among men who have sex with men (MSM) in HIV-seropositive sexual relationships with that among men in HIV-seronegative and serodiscordant relationships in the context of an emerging hepatitis C virus (HCV) epidemic among HIV-positive MSM. Methods: Time-location sampling was used to obtain a cross-sectional sample of MSM who attended public venues in San Francisco between November 2007 and October 2008 (N=1199). Behavioural measures of sexual risk-taking at the level of the sexual dyad were administered to the sample. Results: Men in HIV-positive/positive sexual relationships are significantly more likely to have UAI and combine sex and drugs than men in negative/negative sexual relationships. Conclusions: If it is possible to spread HCV infection between HIV-positive men via UAI, very high levels of behavioural risk among positive MSM should exist to facilitate HCV transmission. Identifying the precise behavioural risk factors for HCV among HIV-positive MSM has become an important public health priority.